Security Stress and the Transformation of the Enemy in Colombia with the End of the Farc-Ep - Niño, César; Palma Álvarez, Daniel (PARTECIPAZIONE E CONFLITTO, 2024)
How does the transformation of the FARC-EP from an enemy to a legitimate political adversary affect the definition of security and its application in Colombia? This question is of great significance, particularly in the context of the security stress experienced by the country after the signing of the 2016 Peace Agreement. Our analysis demonstrates that there is a disconnection between decision-makers and citizen realities, which is affecting territorial security. The orthodox notions of official security operators, the increase in massacres, and the murder of social leaders and ex-combatants who signed the Agreement provide evidence of this phenomenon. To understand the dynamics at play, we conducted a theoretical and empirical study of the years following the signing of the Havana Peace Agreement. Our analysis reveals that security stress is the accumulation of uncertainties generated by the vexations of the conflict on state institutions, as well as social fears of the exacerbation of violence.